STUDI AL-QUR'AN HADIST: Hadits Shahih, Hasan, dan Dhaif - FREDY WAHYU SINGGIH; IMAMUL MUTTAQIN (Darul Ulum: Jurnal Ilmiah Keagamaan, Pendidikan dan Kemasyarakatan, 2024)
Abstract Hadith is one of the foundations for determining law for Muslims. In fact, in terms of legal position, hadith is in a position after the Koran as the highest source of law in Islam. In terms of level, hadith is divided into three, namely: 1) Sahih Hadith, 2) Hasan Hadith, and 3) Daif Hadith. In this article the author will discuss what authentic, hasan, and dhaif hadith are and what conditions readers can use to find out; which hadith is authentic, hasan, or dhaif. By using analysis from several journals and books, it is hoped that this journal can be the key to understanding for readers to better understand what authentic, hasan, and dhaif hadith are. Keyword : Hadith, Hadith Shahih, Hadith Hasan, Hadith Dhaif